HAWSABAH AL-LUGHAH AL-‘ARABIYAH WA TAQDÎM MANHAJ MUQTARAH LAHU FÎ MARKAZ DIRÂSÂT AL-LUGHAH AL-‘ARABIYAH FÎ JÂMI’AH SULTAN ZAINAL ABIDIN TRENGGANU AL-MÂLÎZIYAH - Salem Elawadi, Elsayed Mohamed; Sahrir, Muhammad Sabri bin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2019)
This research aimed at finding out how the orientation is towards Arabic language computing, the efforts contributed to this approach, the difficulties encountered in linguistic computing, and the solutions to these challenges in an applied and theoretical approach at the same time. One of the outputs of the research was to develop a proposed vision and a mission (digitization or computerization of the Arabic language) within the programs of the Arabic language at Sultan Zainal Abidin University in Terengganu, Malaysia. The study concluded several recommendations, the most important was the need for concerted efforts in the field of Arabic computer linguistics between linguists and students, and to spread computer awareness among linguists by encouraging universities to allocate a course on computerization of the Arabic language and creating a new specialization in Arabic language, to develop the linguistic councils in fulfilling the challenges of computerization of Arabic, translating all scientific works written and published in the field of Arabic computer linguistics in foreign languages by Arab and foreign researchers and transferring them into Arabic, creating a dictionary for the computer linguistics terminology in Arabic, and applications of developments of instructional technologies such as machine translation, electronic dictionary and so on.